Research Trend and Future Direction of SMEs Performance Determinants: Literature Review 2014-2024 - Rizkita, Marsya Aulia; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT Aksara Indo Rajawali, 2024)
This article conducts a systematic review of the determinants of Small and Medium Enterprises (SMEs) performance over the period 2010-2024. The method used is a Systematic Literature Review (SLR), utilizing the Scopus database to identify and evaluate relevant articles related to SMEs performance. The main findings of this article indicate that SMEs performance is influenced by two factors, internal and external factors, such as innovation, leadership, financial stability, supply chain management, and government support. Additionally, there are research gaps, such as the need for further exploration of the impact of digital transformation, the role of social media marketing, social sustainability issues, and the interaction between internal and external factors. This article offers future research directions to strengthen SMEs competitiveness in an increasingly competitive and advanced digital era.